Narrative review of metabolomics in cardiovascular disease - Müller, Julian; Bertsch, Thomas; Volke, Justus; Schmid, Alexander; Klingbeil, Rebecca; Metodiev, Yulian; Karaca, Bican; Kim, Seung‑Hyun; Lindner, Simon; Schupp, Tobias; Kittel, Maximilian; Poschet, Gernot; et al. (Journal of thoracic disease, 2021)
Narrative review of metabolomics in cardiovascular disease
Gesehen am 14.07.2021